Service Quality and Innovation as Drivers of Customer Loyalty: The Mediating Role of Customer Satisfaction in the Context of Indonesian Railways - Rahmi, Nurfa Audea; Ridhaningsi, Fitria (Manunggal Halim Jaya, 2026)
The increasingly tight competition in the post-pandemic transportation industry has encouraged service providers to improve service quality and innovate to maintain customer loyalty. This study aims to analyze the effect of service quality and innovation on customer loyalty with customer satisfaction as a mediating variable at PT Kereta Api Indonesia Divre II West Sumatra. A quantitative approach was used through surveys and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, and processed with SmartPLS software. The sample in this study consisted of 180 respondents who were active users of train services in the region. The study's results indicate that service quality and innovation have a positive and significant effect on customer satisfaction, and customer satisfaction significantly mediates the effect of service quality and innovation on customer loyalty. However, the direct effect of innovation on customer loyalty is not significant. This finding suggests that improving service quality and adequate innovation can strengthen satisfaction, which leads to loyalty. This study recommends that PT KAI management focus more on integrating digital services and physical comfort in the customer experience. Theoretically, the results of this study enrich the literature on marketing management in the transportation sector.